Analisis Deskriptif Persepsi Mahasiswa tentang Lingkungan Belajar pada Program Studi Pendidikan Geografi FMIPA Universitas Negeri Gorontalo - Wiwin Kobi; Ronal Tahir; Muhammad Rifqih R. Pango (Geosfera: Jurnal Penelitian Geografi, 2025)
The transformation of higher education in the post-pandemic era and the integration of technology in learning have significantly impacted how students interact with the academic environment. This study aims to analyze students' perceptions of the learning environment in the Geography Education Study Program, FMIPA, Universitas Negeri Gorontalo, focusing on the physical, social, and psychological dimensions. Using a quantitative approach with a descriptive survey design, the study involved 34 students as respondents selected through purposive sampling. Data were collected through a Likert-scale questionnaire to measure perceptions regarding the availability of facilities, room comfort, lecturer-student interaction, as well as motivation and emotional safety in learning. The results showed that 94.1% of respondents considered adequate learning facilities to be a key indicator of a good learning environment, highlighting the importance of the physical quality of classrooms and learning resources. Meanwhile, 47.1% of respondents viewed socioeconomic factors as highly influencing their academic performance, followed by 47.1% who considered noise levels and learning motivation as key psychological factors affecting concentration. These findings suggest that the quality of physical facilities and positive social relationships between students and lecturers are the primary factors supporting academic success, while the quietness of the learning environment and intrinsic motivation also play an essential role in creating a conducive learning ecosystem. This study contributes to the development of strategies to improve the quality of the learning environment in higher education, with practical implications for educational policy development and enhancing the academic experience for students.